Monitoring of Main Outfall Drain and Southern Marsh in Iraq by Arithemitic Water Quality Index - Al-Janabi, Zahraa Zahraw; Maktoof, Afrah A.; Al-Ani, Rana R.; Al-Obaidy, Abdul-Hameed M. Jawad; TA., Mohammed M. (Iraqi Journal of Science, 2025)
This study set out to assess the ecological states to show that the Main Outfall Drain and the Southern Marsh are viable for irrigation use and the preservation of aquatic life. Water quality conditions at four sites were evaluated using the weight model. Samples were taken monthly to calculate the water quality index (WQI) for two seasons, summer of 2021 and winter of 2022. Twenty-six parameters were chosen to apply the WQI: Cl-, CO3-, HCO32-, Ca2+, Mg2+, pH, electrical conductivity (EC), NO3, NO2, NH3, Na+, K+, dissolved Oxygen (DO), water temperature (WT), total dissolved solids (TDS), Mn, Ni, Pb, Fe, Cr, Zn, Cd, Cu, sodium absorption ratio (SAR), residual sodium carbonate (RSC) andsoluble sodium percent (SSP). High levels of Cl, TDS, Cu and Pb were found in all sites during both seasons, and their concentrations were beyond the aquatic life protection criterion. Cl-, Mg2+, pH, EC, Na+, Cu and Cd were above the permissible limit for irrigation uses. The results of the index for protection of aquatic life and irrigation uses ranged between 72.12–372.47 and 131.24–158.1 respectively. The WQI’s ultimate rating ranged from very poor to unfit for both purposes. Therefore, only tolerant species may find this water quality acceptable which is insufficient to support the presence of diverse aquatic life.